2015
DOI: 10.1007/s12351-015-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

Factor-specific Malmquist productivity index based on common weights DEA

Abstract: This paper designs a Malmquist productivity index (MPI) to measure the productivity change of a decision-making unit (DMU) on a specific input/output factor over time. First, factor-specific data envelopment analysis is extended by considering input/output substitution possibilities, where partial correlation is taken as the criterion of substitutability. Factors are clustered and those which are not in the same cluster with the concerned one are excluded when calculating the factorspecific efficiency. Next, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recently, Salahi et al (2016) suggested a robust counterpart model for the envelopment form of CCR, and introduced relations between dual of this model and robust counterpart of multiplier form of CCR. Yang et al (2016) conducted a case study of Taiwan forests after reorganization. For that reason, they constructed a DEA-based common weight decision aid for calculating the change of efficiency scores of a DMU at different time periods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Salahi et al (2016) suggested a robust counterpart model for the envelopment form of CCR, and introduced relations between dual of this model and robust counterpart of multiplier form of CCR. Yang et al (2016) conducted a case study of Taiwan forests after reorganization. For that reason, they constructed a DEA-based common weight decision aid for calculating the change of efficiency scores of a DMU at different time periods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, some scholars have carried out research in the field of the comprehensive evaluation of a low-carbon grid. Carbon emission is taken into consideration for grid planning through the method of super-efficiency data envelopment analysis (SE-DEA) [11]. Existing studies with a particular focus on the Chinese context include, but are not limited to, the following: Tan Wei Existing environmental impact accounting tools such as ecological designs, cleaner production audits, and ISO14001 are mostly principle-based regulations lacking specificity for different industries that have not been widely promoted.…”
Section: Introductionmentioning
confidence: 99%
“…The non-parametric approach concentrates on the regularity assumptions of the production possibility set [54]. Data envelopment analysis (DEA) is a methodology extensively applied in measuring the relative efficiency of decision-making units with multiple inputs and outputs [55,56]. The free disposal hull (FDH) is an alternative deterministic, non-parametric model developed for the evaluation of productive efficiency.…”
Section: Introductionmentioning
confidence: 99%